Women's leadership in agrifood systems: Reflective tool for practitioners - Shijagurumayum, Meghajit; Morgan, Miranda; Hakhu, Arunima; Verma, Benu; Miri, Manjulata; Patibandla, Vinuthna (2024)
In 2024, experts from across different sectors in India came together to share their respective experiences and insights on women’s leadership in agrifood systems. During this process, participants developed a collective vision and co-created a shared learning agenda with key questions to guide future research efforts. They also identified the need for a set of key reflection questions for practitioners to critically reflect on any initiatives or efforts seeking to support women’s leadership. This Reflective Tool is designed for practitioners and researchers who are seeking to advance women’s leadership in agrifood systems. It provides a set of reflection questions to prompt critical reflections and discussions on women’s leadership at key stages of the project cycle.